Development of real-time PCR method for detection of Xanthomonas campestris pv. juglandis causing walnut bacterial blight - Dong, Yuqing; Xie, Ling; Zhu, Hanmingyue; Zhu, Tianhui (Penerbit Universiti Kebangsaan Malaysia, 2024)
Walnut is one of the important economic tree species in the world. For the past few years, with the continuous expansion of walnut planting area, walnut bacterial blight caused by Xanthomonas campestris pv. juglandis has critically affected walnut production and caused economic losses. In this research, by comparing the gene sequences of X. campestris pv. juglandis and its closely related bacterial species, the 16S rDNA gene sequence was selected, and the specific primers were evaluated using PCR. Subsequently, the real-time fluorescence PCR specific detection method of X. campestris pv. juglandis was established and optimized. The specificity of real-time PCR was verified for 23 strains isolated from walnut and its surrounding soil, including eight target pathogens. The specific amplification was possible even when the cDNA template concentration was 7.0×10-5 µg/mL, hence, the detection sensitivity of the standard method is 7.0×10-5 µg/mL. The reliability of the established real-time PCR detection method in field detection was verified by the identification of target bacteria in 8 randomly collected healthy leaves and leaves of suspected walnut blight. This method laid a foundation for the early diagnosis of X. campestris pv. juglandis.